Bursting the (filter) bubble: Interactions of members of parliament on Twitter - Ferro-Santos, S.; Cardoso, G.; Santos, S. (Media e Jornalismo, 2024)
Western European representative democracy models are strongly party-based, generating different incentives for political actors’ communication. Using Portugal as an example, our study analyzes if and how Portuguese Members of Parliament (MPs) interact on twitter, studying their interactions with 757 twitter accounts during one week in four different months. Our study concludes that, although more than half of tweets didn’t have advanced interaction, this type of interaction varies significantly across political parties, which may suggest that party organization may affect their MPs’ communication style. We also conclude that party homophily can be found in some forms of interac- tion but not in others. These results “bursts” the idea that “filter bubbles” are created around values homophily but validates such a claim regarding status homophily as most of the accounts the MPs interacted with (excluding institutional ones) were from the “Twitter Elite”.